2015
DOI: 10.1007/jhep03(2015)016
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the center vortices and vacuum domain in potentials between static sources

Abstract: In this paper, we study the role of the domain structure of the Yang Mills vacuum. The Casimir scaling and N-ality are investigated in the potentials between static sources in various representations for SU(2) and SU(3) gauge groups based on the domain structure model using square ansatz for angle α C (x). We also discuss about the contributions of the vacuum domain and center vortices in the static potentials. As a result, the potentials obtained from vacuum domains agree with Casimir scaling better than the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15], within the infrared effective model of center vortices under investigation here [16][17][18][19][20][21][22][23][24] and another infrared model of random vortex lines in continuous 3D space-time [25,26] and also by theoretical effective model calculations, e.g. [27][28][29][30]. The physical motivation for the vortex picture can be seen from the Wilson loop criterion of confinement, i.e., the expectation value of the Wilson loop has to follow an area law in the confined phase.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15], within the infrared effective model of center vortices under investigation here [16][17][18][19][20][21][22][23][24] and another infrared model of random vortex lines in continuous 3D space-time [25,26] and also by theoretical effective model calculations, e.g. [27][28][29][30]. The physical motivation for the vortex picture can be seen from the Wilson loop criterion of confinement, i.e., the expectation value of the Wilson loop has to follow an area law in the confined phase.…”
mentioning
confidence: 99%
“…Using the thick center vortex model with the idea of vacuum domain structures, Deldar et al have found the potential between static color sources in the G 2 gauge group [5], [6], [7]. Their results are compatible with numerical Lattice calculations for the G 2 gauge group [8], [9], [10], [11].…”
Section: Introductionmentioning
confidence: 72%
“…By adopting the same approach used in Refs. [6], [7] and utilizing Eq. (12), we can reconstruct the Cartan generator H of F 4 for the fundamental 26-dimensional representation: [6]:…”
Section: Thick Center Vortex Model With Trivial and Non-trivial Centementioning
confidence: 99%